Phase and porosity changes in a calcium aluminate cement and alumina system under hydrothermal conditions. Issue 3 (1st February 2023) - Koehler, A.; Rößler, C.; Neubauer, J.; Goetz-Neunhoeffer, F.
Abstract: When refractory castables are dried, hydrothermal conditions may result inside the bodies if the H2 O cannot escape from the material. Under such high-pressure conditions, problems such as explosive spalling can arise. As different curing temperatures during the hydration of calcium aluminate cement (CAC)-bound castables lead to the formation of different hydrate phases, different microstructures can develop in the hardened material. This study presents the changes in porosity and in the mineralogical composition of a refractory castable model system under hydrothermal conditions depending on the curing temperature (5, 23 and 40 °C). Quantitative X-ray diffraction (QXRD) measurements show that different hydrate phases are formed during curing, while C3 AH6 and boehmite are formed in the same quantities after hydrothermal treatment in an autoclave at ∼11 bar/180 °C. Although the mineralogical composition after autoclaving is not different, the three samples differ in their microstructure. Mercury intrusion porosimetry measurements reveal that although the total porosity after autoclaving is the same, the 40 °C samples have a higher proportion of large pores. SEM images also show that the appearance of C3 AH6 in the 40 °C autoclaved samples varies, which originates from the starting phase composition and microstructure after curing.